Transient autoantibodies to danger signals - Shaw, Elana R.; Matzinger, Polly (Frontiers in Immunology, 2023)
The Danger Model predicts that there are some molecules that no immune system can ever be fully tolerant of, namely proteins that are only transiently expressed during times of stress, infection, or injury. Among these are the danger/alarm signals themselves. Accordingly, a fleeting autoantibody response to danger signals is expected during times when they are released. Depending on context, these autoantibodies may serve beneficial “housekeeping” functions by removing surplus danger signals from the circulation or, conversely, create an immunodeficiency. Here, we will focus on the Type 1 Interferons as examples of foreseeable targets for a transient autoantibody response, but the principles outlined should hold for other danger-associated molecules as well.